Analysis of teaching skills in swimming and gymnastics in faculties of physical education - Abdelsalam Jaber Hussein; Loay Mohammad Al-Shawabka; Hasan Jamal Aloran; Walid Al Hammouri; Rama Mohammad Al Sharksi; Waleed Thseen Alaskar; Mohammad Mahmoud Al-Hawari (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.